Ethanol extract of loquat fruit skin inhibits the proliferation and metastatic potential of EJ human bladder carcinoma cells. Issue 5 (3rd September 2017) - Shin, Seung-Shick; Hwang, Byungdoo; Lee, Soo-Bok; Kim, Wun-Jae; Moon, Sung-Kwon
ABSTRACT: Although studies on biological properties of loquat plant have been performed, research on the molecular mechanism of action in loquat fruit skin is very limited. Therefore, we investigated the molecular mechanisms underlying the inhibitory activity of ethanol extract from loquat fruit skin (EEFS) against the proliferation and metastatic potential of EJ bladder carcinoma cells. Treatment of EJ cells with EEFS significantly inhibited their proliferation by inducing cell-cycle arrest at the G1 phase. Expression of CDK2, CDK4, cyclin D1, and cyclin E was altered by EEFS treatment. Interestingly, p27KIP1, but not p21WAF1 or p53, was identified as a candidate CDK inhibitor (CDKI) associated with the EEFS-mediated inhibition of proliferation. Among mitogen-activated protein kinases, ERK1/2 phosphorylation was significantly elevated but not that of p38 and JNK. In addition, phospho-AKT (protein kinase B; PKB) was not affected by EEFS treatment. Aggressive phenotypes, including migratory and invasive potentials of EJ cells, were similarly diminished by EEFS. Gelatin zymography showed that the enzymatic activity of matrix metalloproteinase (MMP)-9 was markedly inhibited by treatment with EEFS. Results from electrophoretic mobility shift assays demonstrated that MMP-9 inhibition was associated with reduced binding activities of transcription factors NF-κB, activator protein-1, and specificity protein 1 to its promoter region. Taken together, our data clearly indicate that EEFS inhibits the proliferation of EJ cells through p27KIP1, which is associated with G1 arrest and increased extracellular signal-regulated kinase phosphorylation. Metastatic potential represented by MMP-9 activity was also remarkably inhibited by EEFS, suggesting that EEFS is a novel chemotherapeutic agent for bladder cancers.